Environmental Attitudes of Scientists in Ghana, Kenya, and Kerala: Evidence on NGOs and Traditional Research Sectors - Patricia Campion and Wesley Shrum (Journal of Asian and African Studies 2002; 37; 17, 2002)
Drawing on a survey of researchers in Ghana, Kenya, and the Indian state of Kerala, attitudes of NGO scientists are examined and compared with those in universities and national research institutes. Recently, some NGOs have initiated research activities, raising the question of whether those who pursue research in these organizations are similar to or different from those in more traditional contexts. Environmentalist views are now widespread among researchers in less developed countries. Two underlying Dimensions are identified, one of which is tiers-mondisme, the degree to which a researcher adopts a distinctive developing country perspective on environmental issues. Results show that NGO researchers are not generally different in terms of their Environmental views. However, national context and participation in the international system affect the degree to which researchers adopt a distinctive developmental perspective.